2022
DOI: 10.3389/fpsyt.2022.1022144
|View full text |Cite
|
Sign up to set email alerts
|

Delayed sleep-wake rhythm is associated with cognitive dysfunction, social dysfunction, and deteriorated quality of life in patients with major depressive disorder

Abstract: BackgroundThe delayed sleep-wake phase is commonly observed in major depressive disorder (MDD) and thought to be associated with functional impairments. This study aimed to evaluate the relationship between the delayed sleep-wake phase, cognitive dysfunction, social dysfunction, and quality of life in patients with MDD.MethodsThis cross-sectional design included 33 outpatients with MDD. Objective sleep-wake rhythm was assessed by actigraphy. Functional impairments were evaluated by the Japanese version of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Delayed sleep phase disorder can result in impaired functioning during the daytime, a chronic lack of sleep, and an increased risk of affective disorders. One key domain of impaired functioning with loss of sleep is memory ( Takaesu et al, 2022 ). In one relevant study, adolescents with delayed sleep phase disorder showed an improvement in memory-related cognition tasks after receiving 3 weeks of light therapy to help entrain them to regular circadian rhythm ( Richardson et al, 2018 ).…”
Section: Acute and Chronic Effects Of Disruptions In Sleep And Circad...mentioning
confidence: 99%
“…Delayed sleep phase disorder can result in impaired functioning during the daytime, a chronic lack of sleep, and an increased risk of affective disorders. One key domain of impaired functioning with loss of sleep is memory ( Takaesu et al, 2022 ). In one relevant study, adolescents with delayed sleep phase disorder showed an improvement in memory-related cognition tasks after receiving 3 weeks of light therapy to help entrain them to regular circadian rhythm ( Richardson et al, 2018 ).…”
Section: Acute and Chronic Effects Of Disruptions In Sleep And Circad...mentioning
confidence: 99%
“…It has also been reported that various mental disorders, including major depression, are associated with sleep problems [ 3 5 ]. In addition, sleep loss interferes with cognitive function [ 6 9 ] and emotion regulation [ 10 13 ], resulting in difficulties in social adjustment [ 14 ]. Therefore, getting sufficient sleep at the appropriate time is essential not only for individuals’ health but also for socioeconomic benefits.…”
Section: Introductionmentioning
confidence: 99%
“…There is some solid evidence for a connection between circadian rhythm disorder and neurologic diseases such as Alzheimer’s and Parkinson’s disease ( Gu et al, 2015 ; Weissova et al, 2016 ; Richmond and Davey Smith, 2022 ). It is also linked to mental illnesses such as bipolar disorder, depression, and anxiety, and to disorders such as autism ( Walker et al, 2021 ; Martinez-Cayuelas et al, 2022 ; Takaesu et al, 2022 ; Ketchesin et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%